2018
DOI: 10.1111/fme.12304
|View full text |Cite
|
Sign up to set email alerts
|

Using a telemetry study to assess the boundary net efficiency of an enclosure system used for yellow eel density monitoring

Abstract: To assess yellow eel (Anguilla anguilla L.) densities in non‐tidal waters, 1‐ha enclosure approach was developed. For unbiased density and biomass calculations, the catchability of the system needs to be evaluated. A telemetry study with 49 tagged eels was conducted in 2015 and 2016 to verify the effectiveness of the 1.8‐m high boundary net. Excluding recaptured eels (N = 10), 42.8% of the released eels (N = 15) escaped the enclosure within 48 hr. Regarding the movement frequency, similar movement patterns wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Because boundary net float lines are typically below the water surface, eels are capable of entering or exiting the enclosure. A telemetry study in 3 m of water found that enclosed eels moved along, or away from, the boundary net, but that 43% of non‐recaptured eels left the enclosure within 48 h (Dorow et al, 2019). However, this study was conducted without fyke net chains, which are responsible for 79% of eel captures in standard enclosure deployments.…”
Section: Novel Ideas and Underutilised Resourcesmentioning
confidence: 99%
“…Because boundary net float lines are typically below the water surface, eels are capable of entering or exiting the enclosure. A telemetry study in 3 m of water found that enclosed eels moved along, or away from, the boundary net, but that 43% of non‐recaptured eels left the enclosure within 48 h (Dorow et al, 2019). However, this study was conducted without fyke net chains, which are responsible for 79% of eel captures in standard enclosure deployments.…”
Section: Novel Ideas and Underutilised Resourcesmentioning
confidence: 99%
“…For yellow eels in coastal waters, the 1-ha enclosure approach of Ubl and Dorow (2015) seems to hold promise. As the yellow eel-specific catchability is known (Dorow et al, 2019(Dorow et al, , 2020, the standardised use of the enclosure approach would allow the detection of trends in yellow stocks as well as transferring observed densities data to true yellow eel density estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies used telemetry to investigate individual movement patterns, site fidelity, habitat use and home range exploitation in relation to seasonal and environmental factors (e.g., Ovidio et al, 2013;Barry et al, 2015;Piper et al, 2017;Trancart et al, 2018;Dorow et al, 2019;Piper et al, 2019;Teichert et al, 2020).…”
Section: Habitat Occupancymentioning
confidence: 99%
“…Direct observations of the migratory behavior of yellow and silver eels were made using electronic tags (e.g., Amilhat et al, 2016;Righton et al, 2016;Béguer-Pon et al, 2018;Dorow et al, 2019;Teichert et al, 2020;Trancart et al, 2020). Telemetry represents a reliable method to study the spatial ecology of eels, providing the opportunity to track fish in real time or from archived data to remote receivers, enabling data to be retrieved without recapturing the tag (Torstad et al, 2013).…”
Section: Adult Migration Behaviormentioning
confidence: 99%